(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Like other registers, American journalistic texts, including newspapers, are characterized by certain textual and stylistic features. They often have their own organization, wording, choice of vocabulary, syntactic structures, etc.News writers usually tend to manipulate language to achieve their own goals. They often use special expressions to shape or frame readers’ emotions and ideologies into certain direction, to achieve certain effects that can help to change their attitude. To achieve their aims, news writers may use various devices. They may even deviate from language norms to attract reader’s attention. Among the textual syntactic devices used in newspaper are null constituents. This paper is an attempt to study null constituents in selected news articles quoted from five American newspapers: New York Times, The Washington Post, The wall street Journal, USA Today, and Houston Chronicle. The study aims at finding out the extent to which null constituents are employed in these articles, the purposes behind using them as well as finding out the most and least frequent types of these constituents. The results of analyzing the selected articles show that that Cnull and Auxnull are the most frequent null constituents in the headlines of news articles. As for the body of the articles, the results show that S null is the most frequent null constituent in the body of news articles. Auxnull has been found to be the least frequent in the body of news articles.